Construction sites and subjective Quality Of Life assessment: case of Ali Mendjeli, Algeria - GHEDJATI , Zakaria; SASSI BOUDEMAGH , Souad (Journal of Human Sciences, 2022)
The Quality Of Life (QOL) is a multidimensional concept defined as individuals perception of the living conditions including subjective evaluations of their well- being in different aspects. These perceptions may be intensified in complex urban settings. Furthermore, the existence of construction sites in an urban context distorts its characteristics, which may affect QOL. In this article, a subjective assessment method is conducted, in the new city of Ali Mendjeli, to evaluate the impact of the tramway construction site on (QOL). Results show that the construction sites have negative impacts on the (QOL) of the city inhabitants and users in different aspects.